Global patterns of the effects of land-use changes on soil carbon stocks - Deng, Lei; Zhu, Guang-yu; Tang, Zhuang-sheng; Shangguan, Zhou-ping (Global ecology and conservation, 2016)
Despite hundreds of field studies and at least a dozen literature reviews, there is still considerable disagreement about the direction and magnitude of changes in soil C stocks with land use change. This paper reviews the literature on the effects of land use conversions on soil C stocks, based on a synthesis of 103 recent publications, including 160 sites in 29 countries, with the aims of determining the factors responsible for soil C sequestration and quantifying changes in soil C stocks from seven land use conversions. The results show that as an overall average across all land use change examined, land use conversions have significantly reduced soil C stocks (0.39 Mg ha−1 yr−1). Soil C stocks significantly increased after conversions from farmland to grassland (0.30 Mg ha−1 yr−1) and forest to grassland (0.68 Mg ha−1 yr−1), but significantly declined after conversion from grassland to farmland (0.89 Mg ha−1 yr−1), forest to farmland (1.74 Mg ha−1 yr−1), and forest to forest (0.63 Mg ha−1 yr−1). And after conversion from farmland to forest and grassland to forest, soil C stocks did not change significantly. Globally, soil C sequestration showed a significant negative correlation with initial soil C stocks (P<0.05), and the effects of climatic factors (mean annual temperature and mean annual precipitation) on soil C sequestration varied between the land use conversion types. Also, the relationships between soil C sequestration and age since land use conversion varied in different land use change types. Generally, where the land use changes decreased soil C, the reverse process usually increased soil C stocks and vice versa. Soil C sequestration dynamics were not determined by age since land use conversion at the global level when all land use change types were combined.